2018
DOI: 10.1093/infdis/jiy422
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 1–Targeting Small-Molecule C31 Inhibits Ebola Virus Replication

Abstract: C31 represents a novel PP1-targeting EBOV inhibitor with improved pharmacological properties that can be further evaluated for future antifiloviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…We recently showed that 1E7-03, a PP1-targeting compound was degraded in vivo (Lin et al, 2017). Its degradation products were not cell permeable, and thus lacked EBOV inhibitory activity (Ammosova et al, 2018). To improve the metabolic stability of 1E7-03, we designed several analogs (Figure 1A) based on the 1E7 lead compound that was initially used to develop 1E7-03 (Ammosova et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently showed that 1E7-03, a PP1-targeting compound was degraded in vivo (Lin et al, 2017). Its degradation products were not cell permeable, and thus lacked EBOV inhibitory activity (Ammosova et al, 2018). To improve the metabolic stability of 1E7-03, we designed several analogs (Figure 1A) based on the 1E7 lead compound that was initially used to develop 1E7-03 (Ammosova et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…To improve the metabolic stability of 1E7-03, we designed several analogs (Figure 1A) based on the 1E7 lead compound that was initially used to develop 1E7-03 (Ammosova et al, 2014). The lead 1E7 compound (reported as T5236177 or compound 63) inhibited EBOV but was found to be toxic and excluded from further evaluation (Ammosova et al, 2018). The 1E7-based library was designed based on the following criteria (i) position 4 in tetrahydroacridine ring must tolerate small aromatic groups; (ii) the saturated ring in the core must be unsubstituted; and (iii) only flexible linear linkers enriched with hydrogen bonding functionalities are acceptable at position 9 (see more details in Ammosova et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations